Back to the Basics: Socio-Economic, Gender, and Regional Disparities in Canada’s Educational System - Edgerton, Jason; Peter, Tracey; Roberts, Lance (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
This study reassessed the extent to which socio-economic background, gender, and region endure as sources of educational inequality in Canada. The analysis utilized the 28,000 student Canadian sample from the data set of the OECD’s 2003 Programme for International Student Assessment (PISA). Results, consistent with previous findings, highlight the uneven distribution of educational achievement in Canada along socio- economic, gender, and regional lines, and point to the continued necessity of policy to mitigate the impact of gender, class, and regional inequalities on the educational out- comes and life chances of young Canadians. Key words: social inequality, educational outcomes, educational aspirations, SES, cultural capital, PISA Dans cet article, les auteurs se demandent dans quelle mesure le statut socioéconomi- que, le sexe et la région demeurent des sources d’inégalité en matière d’éducation au Canada. L’analyse repose sur l’échantillon des 28 000 élèves canadiens tiré de l’ensemble de données du Programme international pour le suivi des acquis des élèves (PISA) de 2003 de l’OCDE. Les résultats, conformes aux conclusions antérieu- res, mettent en évidence la répartition inégale de la réussite scolaire au Canada selon le statut socioéconomique, le sexe et la région et indiquent la nécessité d’atténuer l’impact du sexe, de la classe sociale et des inégalités régionales sur les résultats scolaires et les chances d’épanouissement des jeunes canadiens. Mots clés : inégalité sociale, résultats scolaires, aspirations quant aux études, statut socioéconomique, capital culturel, PISA